2004
DOI: 10.1016/j.jacc.2003.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with double-inlet left ventricle or tricuspid atresia with transposed great arteries

Abstract: The mortality of patients with DILV or TA-TGA remains high. The outcomes of these patients are influenced by restriction of pulmonary blood flow, arrhythmia, and pacemaker requirement. Surgical palliation to relieve systemic outflow obstruction is not associated with a poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…In a recent study by the same group, Lan et al suggested that systemic obstruction associated with a gradient but without ventricular hypertrophy, does not influence longterm outcome [8].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In a recent study by the same group, Lan et al suggested that systemic obstruction associated with a gradient but without ventricular hypertrophy, does not influence longterm outcome [8].…”
Section: Discussionmentioning
confidence: 98%
“…This strategy requires close observation of the subaortic and aortic area and an early DKS procedure should obstruction develop [4][5][6][7][8]. Using a vigorous surveillance to detect subaortic obstruction, Odim et al were able to recognise early development of subaortic obstruction in 8 of 15 patients following pulmonary artery band [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations